Discourse Issues Three Periods of Jokowi's Leadership (Norman Fairclough's Critical Discourse Analysis in Kompas.com News Text) - Nisa Haerunisa; Teti Sobari (IKIP Siliwangi, 2023)
This research is motivated by the development of issues regarding the three periods of Jokowi's leadership in society. The issue of this discourse does not only appear once but many times, giving rise to pros and cons. This issue has even sparked a wave of mass action in several areas. The purpose of this research is to describe President Jokowi's attitudes and responses to the three-period issue discourse in the Kompas.com news text. The method used in this study uses a qualitative approach with the type of critical discourse analysis research. The researcher uses Norman Fairclough's critical discourse analysis. This text is analyzed in terms of language, vocabulary, semantics, and grammar (micro). Text can also be analyzed through how the text is produced and the things that build it (meso). The text can also be analyzed from the socio-cultural influences that make up the text (macro). The results of the study show that the issue of this discourse was not only announced once but many times. Then there is President Jokowi's response and attitude which is not the same as responding to it. Through the choice of words displayed by journalists, Kompas.com media indirectly wants to present a negative image. From a news perspective, Kompas.com wants to capture the problems and realities that occur on the ground. Kompas.com displays hot and actual news by compiling previous events so that they become complete and comprehensive news. This automatically makes it easier for the reader to understand the construction of a story. The issue of discourse on the three periods is reminiscent of the power practices during the Old Order and New Order periods, where the constitution was not implemented properly so the term limits for the president were distorted.